2016
DOI: 10.4067/s0717-92002016000300019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of calafate (Berberis buxifolia) seeds

Abstract: Thermal behavior of calafate (Berberis buxifolia) seedsComportamiento térmico de las semillas de calafate (Berberis buxifolia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…It can be observed that they are closely related, in particular those of Salvia hispanica and Nigella sativa species. The relationship with the spectra of calafate (Berberis buxifolia L.) 26 and rosehip (Rosa rubiginosa L.) 27 seeds, also included in Table 2 for comparison purposes, is also very high. The highest absorbance for the three spectra occurred at 1022 cm -1 .…”
Section: Vibrational Characterizationmentioning
confidence: 86%
“…It can be observed that they are closely related, in particular those of Salvia hispanica and Nigella sativa species. The relationship with the spectra of calafate (Berberis buxifolia L.) 26 and rosehip (Rosa rubiginosa L.) 27 seeds, also included in Table 2 for comparison purposes, is also very high. The highest absorbance for the three spectra occurred at 1022 cm -1 .…”
Section: Vibrational Characterizationmentioning
confidence: 86%
“…The main endotherm at 109°C corresponds to dehydration and protein denaturation. The second endotherm, with a peak at 209°C, can be attributed to melting of the carbohydrates and other components [16][17][18]. The enthalpy of these effects was found to be 174.4 and 36.17 J/g, respectively.…”
Section: Abrus Precatorius L Seedsmentioning
confidence: 99%
“…La primera experiencia de radicalización estudiantil la encontraremos desde diciembre de 1966 y, especialmente, durante los primeros meses de 1967, cuando, finalmente, prácticamente la totalidad del comité de estudiantes del PSUC -el partido que hasta el momento había actuado como dirigente del movimiento universitario-abandonará el partido con la escisión del grupo «unidad» (posteriormente formarán el PCE(i)). 70 Esta escisión, por lo que se refiere a los estudiantes encontrará entre sus causas la diferente lectura que el grupo escindido y la dirección del partido hacían de la situación tanto nacional como universitaria. Y, aunque no tendrá un gran impacto a nivel cuantitativo, marcará el fin de la hegemonía del PSUC en el movimiento universitario y tendrá una clara influencia en la radicalización del resto de grupos, introduciendo en la universidad los principales debates ideológicos que se están produciendo en el movimiento comunista internacional.…”
unclassified